2012
DOI: 10.1002/path.4058
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wnt signalling promotes development of dysplasia in Barrett's oesophagus

Abstract: Barrett's oesophagus is a precursor of oesophageal adenocarcinoma, via intestinal metaplasia and dysplasia. Risk of cancer increases substantially with dysplasia, particularly high-grade dysplasia. Thus, there is a clinical need to identify and treat patients with early-stage disease (metaplasia and low-grade dysplasia) that are at high risk of cancer. Activated Wnt signalling is critical for normal intestinal development and homeostasis, but less so for oesophageal development. Therefore, we asked whether abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…With respect to the tumorigenic nature of aberrant Wnt-signaling activation (37) and the senescenceassociated tumor suppression, Dkk1 may also play a pivotal role in esophageal carcinogenesis. Although high levels of Dkk1 expression have been reported in EAC (9) and aberrant activation of Wnt/␤-catenin signaling has been found to promote esophageal intestinal metaplasia (27) and neoplastic progression toward EAC (6,4,34), the exact role of Dkk1 during esophageal carcinogenesis remains unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the tumorigenic nature of aberrant Wnt-signaling activation (37) and the senescenceassociated tumor suppression, Dkk1 may also play a pivotal role in esophageal carcinogenesis. Although high levels of Dkk1 expression have been reported in EAC (9) and aberrant activation of Wnt/␤-catenin signaling has been found to promote esophageal intestinal metaplasia (27) and neoplastic progression toward EAC (6,4,34), the exact role of Dkk1 during esophageal carcinogenesis remains unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the wnt/β-catenin signaling pathway plays an important role in cell-cell adhesion. Activation of β-catenin due to mutations and/or overexpression of components of the β-catenin pathway have been associated with several tumours, including colorectal cancer35, lung cancer36, breast cancer37, as well as gastric3839 and esophageal adenocarcinoma4041. Increased expression of transcription factor MYB has been reported in many human cancers42, including esophageal adenocarcinoma43.…”
Section: Resultsmentioning
confidence: 99%
“…They also found that factitious expression of Wnt signal pathway in mouse oesophagus could cause tissue disorganization (125). Their results indicated that Wnt signal pathway plays an initiative effect in ESCC.…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 97%
“…Moyes et al (125) have reported that the expression of nuclear activated β-catenin was highly expressed in high grade of dysplasia when compared with that in Barrett's metaplasia. They also found that factitious expression of Wnt signal pathway in mouse oesophagus could cause tissue disorganization (125).…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%